Orientação de falhas presentes em testemunhos de sondagens do campo de Xaréu/bacia do Ceará - Dominguetti, Cristina Aparecida (2002)
A research project is being developed by PPGG/UFRN and PETROBRAS in the Xaréu Oil Field located in Ceará Basin, Northeastern Brazil. The objective of the research is to characterize a fractured carbonate reservoir, the Trairi Limestone, in order to drill a borehole with two horizontal legs taking advantage of the natural fracture system to enhance the oil recovery. The present master thesis is part of this research and its contribution is to estimate fault orientation from unoriented cores, using the method proposed by Hesthammer & Henden (2000). In order to orient a fault cutting a bed observed in the core, the bed should be previously oriented. As additional constraint to orient the bed, we use regional bedding orientation obtained from structure maps of Trairi Limestone. Because the number of cores drilled from the Trairi Limestone was too small, we analyzed all cores from the field. As geologic constraint, we admit that all faults were formed as result of the South America and Africa separation, in the context of a regional dextral strike-slip fault formation. In this context, secondary faults are manly T and R faults according Riedel s classification. We analyzed 236.5 m of cores. The dip of bedding varies from 0o to 8o, being the most frequent value equal to 2o. We interpret this result as evidence that the deformation process was manly ruptil. 77 faults were identified in the cores. These faults strike manly to NW and NE with dips, in general, inside the interval 700 - 900. We suggest that the horizontal legs of the borehole should be oriented to NW and NE in order to improve the probability of intercepting open fractures and faults